Legalitas Lelang Melalui Aplikasi Lelang Yang Tidak Terdaftar Di Direktorat Jenderal Kekayaan Negara - Liviana Faiza; Aisyah Ayu Musyarafah (Fakultas Hukum Universitas Islam Malang, 2023)
Auction through the auction application is a continuous innovation in today's digital era. In addition, there are auctions through auction applications that are not registered on Direktorat Jenderal Kekayaan Negara. This paper aims to describe the legality of auction activities carried out with these unregistered applications. This study uses a normative juridical method with a statutory approach. The results of the study show that the legality of conducting auctions through auction applications that are not registered in Direktorat Jenderal Kekayaan Negara is invalid because they are not in accordance with the auction regulations in force in Indonesia and result in no protection and guarantee of legal certainty because the loss of the role of auction officials and authentic evidence in the form of minutes of auctions that have perfect evidentiary power.